Influence of some insecticide sequences on the injurious insect- pests of cotton plants - Ismail, Seham M. (2021)
The highest reduction percentages are effective sequences 7 and 5 (gave about 90% infestation reduction) were started and mediated with new insecticides, and when started and mediated with spinosad, or with cypermethrin, sequences 2 and 3 (gave about 86%) respectively, also, the repetition of the same insecticide twice in a regimen might increase, might decrease, or has no effect on the insecticide efficiency against cotton bollworms. The tested sequence programs showed high protection for green bolls with protection percentages ranged from 66.1 and 67.2% (sequence 1) to 92.6 and 94.1% (sequence 7) during two seasons respectively. On the other hand, the superiority in yield loss reduction can arrange in the following descending order: sequences 7, 5, 2, 3, 6, 4, and 1 respectively.